Parkinson’s Disease Medication Adherence Scale: Conceptualization, Scale Development, and Clinimetric Testing Plan - Tosin, Michelle H. S.; Goetz, Christopher G.; Bispo, Dharah P. C. F.; Ferraz, Henrique B.; Leite, Marco Antonio A.; Hall, Deborah A.; Stebbins, Glenn T.; Oliveira, Beatriz Guitton R. B. (Frontiers in Aging Neuroscience, 2022)
Background: Medication adherence is a crucial component in the management of patients with chronic diseases needing a long-term pharmacotherapy. Parkinson's disease (PD) is a chronic, degenerative disease with complex drug treatment that poses challenging barriers to patient adherence. The adoption of best practices of scale development can contribute to generate solid concepts and, in the long run, a more stable knowledge base on the underlying constructs of medication adherence in PD measured by the items of the first scale to be created for this purpose. Purpose: To present the development process and clinimetric testing plan of the Parkinson's Disease Medication Adherence Scale (PD-MAS). Method: We adopted a hybrid approach plan based on the United States Food and Drug Administration and Benson & Clark Guide that will create a patient-reported outcome instrument. We presented an overview of consecutive and interrelated steps, containing a concise description of each one. International research centers from Brazil and United States were initially involved in the planning and implementation of the methodological steps of this study. Results: We developed a four-phase multimethod approach for the conceptualization and the clinimetric testing plan of the PD-MAS. First, we describe the development process of the conceptual framework of the PD-MAS underpinning the scale construct; second, we formalized the development process of the first version of the PD-MAS from the generation of item pools to the content validation and pre-testing; third, we established the steps for the first pilot testing and revision; fourth, we describe the steps plan for the first pilot testing and revision, to finally describe its clinimetric testing plan and validation. Conclusion: The overview presentation of the development phases and the clinimetric testing plan of the PD-MAS demonstrate the feasibility of creating an instrument to measure the multidimensional and multifactorial components of the medication adherence process in people with PD.